George S. Denison papers - Denison, George S. (George Stanton), 1833-1866.
Correspondence, including that with family members in Vermont detailing northern views on social conditions in the South prior to the Civil War, memoranda, reports, drafts and printed copies of articles, and broadsides. The bulk of the material relates to Denison's life and work as a lawyer in San Antonio, Tex., as collector of internal revenue in New Orleans, La. (1862-1865), and as supervising special agent of the Treasury Dept. in Texas (1865-1866). Correspondents include Salmon P. Chase.
Lawyer and civil servant.
Collection material in English.
Keywords: Chase, Salmon P. -- 1808-1873 -- Correspondence; United States. -- Department of the Treasury -- Officials and employees; United States. -- Internal Revenue Service -- Officials and employees; Practice of law -- Texas -- San Antonio; Taxation -- Louisiana -- New Orleans; Southern States -- Social conditions; United States -- Officials and employees -- Louisiana; United States -- Officials and employees -- Texas; Vermont -- History -- Civil War, 1861-1865.; Civil servants; Lawyers